A Standardized Classification for Subdural Hematomas- I - Alves, JL (2016)
Subdural hematomas are a frequent and highly heterogeneous traumatic disorder, with significant clinical and socioeconomic consequences. In clinical and medicolegal practice, subdural hematomas are classified according to its apparent age, which significantly influences its intrinsic pathogenic behavior, forensic implications, clinical management, and outcome. Although practical, this empirical classification is somewhat arbitrary and scarcely informative, considering the remarkable heterogeneity of this entity. The current research project aims at implementing a comprehensive multifactorial classification of subdural hematomas, allowing a more standardized and coherent assessment and management of this condition. This new method of classification of subdural hematomas takes into account its intrinsic and extrinsic features, using imaging data and histopathological elements, to provide an easily apprehensible and intuitive nomenclature. The proposed classification unifies and organizes all relevant details concerning subdural hematomas, hopefully improving surgical care and forensic systematization.